Shareholder Voting and Corporate Governance Around the World - Iliev, Peter; Lins, Karl V.; Miller, Darius P.; Roth, Lukas (Review of Financial Studies, 2015)
Using a sample of non-U.S. firms from 43 countries, we investigate whether laws and regulations as well as votes cast by U.S. institutional investors are consistent with an effective shareholder voting process. We find that laws and regulations allow for meaningful votes to be cast, as shareholder voting is both mandatory and binding for important elections. For votes cast, we find there is greater dissent voting when investors fear expropriation. Further, greater dissent voting is associated with higher director turnover and more M&A withdrawals. Our results suggest that shareholder voting is an effective mechanism for exercising governance around the world.